2020
DOI: 10.1177/1464420720904606
|View full text |Cite
|
Sign up to set email alerts
|

Static and dynamic behavior of steel-reinforced epoxy granite CNC lathe bed using finite element analysis

Abstract: Machine tools are used to manufacture components with desired size, shape, and surface finish. The accuracy of machining is influenced by stiffness, structural damping, and long-term dimensional stability of the machine tool structures. Components machined using such machines exhibit more dimensional variations because of the excessive vibration during machining at higher speeds. Compared to conventional materials like cast iron, stone-based polymer composites such as epoxy granite have been found to provide i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Chinnuraj et al [17], Venugopal et al [29] and [30] carried out investigations on the application of SREG structures to CNC lathe and VMC. Static and dynamic investigations have revealed that the use of SREG structures in machine tools will enhance the static and dynamic performance of the machine.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Chinnuraj et al [17], Venugopal et al [29] and [30] carried out investigations on the application of SREG structures to CNC lathe and VMC. Static and dynamic investigations have revealed that the use of SREG structures in machine tools will enhance the static and dynamic performance of the machine.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The objective of this work is to study the influence of the bi-material effect (different thermal properties) of steel and EG on the thermal behaviour of the lathe, in comparison to that of the lathe with the existing cast iron bed. In this work, investigations on the thermal behaviour of a CNC lathe built with an SREG bed have been carried out as a continuation of the static and dynamic investigations of this lathe presented by Chinnuraj et al [17]. The thermal error associated with SREG structures must be investigated in order to obtain the full benefits of the thermally inert, high damping tailor-made EG material.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Collapse of buildings during earthquakes causes serious casualties and economic losses. Much research has been carried out on recent years carried out by Chinese and foreign experts on the mechanical properties and stability of the string dome structure, such as seismic response and anti-seismic analysis [5][6][7][8], buckling and dynamic response under friction [9], model optimization design based on artificial neural networks [10], elastoplastic dynamic response [11], structural optimization algorithm and design [12][13][14], long-span discontinuous mechanical properties [15], initial geometric defect analysis [16], cable tension estimation [17], static and the dynamic analysis by finite element method [18,19], and thrust line analysis of masonry domes [20]. Gong, S.Y.…”
Section: Introductionmentioning
confidence: 99%